Effects of co-management on technical efficiency and environmental stressors: An application to small-scale shrimp polyculture in Indonesia. Issue 1 (2nd January 2022) - Hukom, Venticia; Nielsen, Rasmus; Nielsen, Max
Abstract: Shrimp polyculture is an important activity in South East Asia, providing a livelihood and food for small-scale farmers. However, farmers are facing challenges due to increasing environmental problems in rivers used as the primary source of water in aquaculture pond production. To deal with these challenges, farmers have organized co-management communities, which gives them a stronger voice among river users. This study investigates the effects of co-management on technical efficiency and environmental stressors using a second-stage Data Envelopment Analysis model. Environmental stressors are identified through interviews with 306 farmers in eight sub-districts, of which two are practicing co-management. The results show that farmers in areas with co-management have relatively high technical efficiency after taking other drivers into account. Furthermore, the farmer's technical efficiency seems to be less affected by the identified environmental stressors. In conclusion, co-management could be used as a tool to improve technical efficiency and limit stress factors for farmers. It could be initiated by the farmers themselves or by policymakers and natural resource managers and could improve the livelihoods of small-scale shrimp polyculture farmers.